The Influence of e-WOM, Fashion Trends, and Income on the Consumption Style of the Muslim Community in Palopo City: A Quantitative Analysis - Amiruddin, Rifdayanti; Abdullah, Muh. Ruslan; Noor Bakri, Adzan (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2024)
This study aims to examine the influence of electronic word of mouth (e-WOM), fashion trends, and income on the consumption style of the Muslim community in Palopo City, Indonesia. Utilizing a quantitative approach with data from 126 respondents aged 18–32 years and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), the research confirms that all three variables significantly affect consumption style. Fashion trends exhibit the strongest influence, followed by income and e-WOM. The findings highlight how digital culture, particularly fashion content on social media, reshapes consumer identity and behavior among young Muslims, often transcending traditional income-based consumption models. This research contributes to global consumer studies by integrating Islamic socio-cultural dimensions with digital sociology and consumer culture theory. It provides evidence that aspirational and performative consumption—mediated by influencers and online peer reviews—is increasingly prevalent in urban Muslim communities. The study recommends future research to explore longitudinal changes in digital consumption behavior, assess moderating variables such as religiosity and digital literacy, and conduct cross-cultural comparisons to evaluate the universality of these patterns across Muslim-majority and minority contexts.